PWE-056 Rosiglitazone: a potential new stroma targeted therapeutic agent in colon cancer. (June 2019) - Tabuso, Maria; Adya, Raghu; Christian, Mark; Arasaradnam, Ramesh P
Abstract : Introduction: The impact of tumour associated stroma on cancer cell invasion and metastasis is an attractive emerging field. Using Nanostring Pancancer pathway we have previously identified pro-fibrotic genes collagen type 1, alpha 1 (COL1A1), fibroblast growth factor 7 (FGF7) and secreted frizzled related protein 2 (SFRP2) significantly up regulated in human colon cancer peritumour adipose tissue compared to distal adipose tissue. Aim of this study was to evaluate the effect of Rosiglitazone, a peroxisome proliferator-activated receptor gamma (PPARG) agonist known to have anti fibrogenic properties, on COL1A1, FGF7 and SFRP2. Methods: The effect of Rosiglitazone on COL1A1 and SFRP2 was evaluated employing in vitro co-culture systems. 3T3 L1 murine adipocytes were co-cultured with HCT 116 colon cancer cells with and without 1 nM Rosiglitazone for 72 hours. COL1A1, FGF7 and SFRP2 expression were evaluated using quantitative real time-polymerase chain reaction (qRT-PCR). Statistical analysis was performed using paired Student's t-test with a cut-off of p-value <0.05. Results: Both COL1A1 and SFRP2 resulted significantly downregulated in co-cultured 3T3 L1 adipocytes treated with Rosiglitazone compared to untreated co-cultured 3T3 L1 adipocytes (20 fold change, p=0.02; 3.3 fold change, p=0.01 respectively). We did not observe any significant effect of Rosiglitazone on FGF7 expression in treated 3T3 L1 adipocytes compared to untreated adipocytes. Conclusion: Our results have demonstrated significant down regulation of pro-fibrotic genes COL1A1 and SFRP2 in mature adipocytes induced by Rosiglitazone. Rosiglitazone may represent a novel therapeutic agent in stromal targeted therapy in colon cancer.